Women, Migration and Activism in Europe - Jane Freedman (Amnis)
This paper will focus on the activism of women migrants in contemporary Europe, analysing the ways in which gendered patterns of migration have placed women in particular situations with regard to migration and integration into European societies, and how these women have become activists to claim their rights within these societies. In particular the paper will focus on the struggles of undocumented women migrants who face specific barriers to achieving their rights which may well differ from those of their male compatriots, for example in relation to their more « invisible » labour market presence within the sphere of domestic and care work. Further women migrants may face opposition in their activism from male migrants who feel that women are overstepping their traditional roles in taking on actively political stances. The paper will engage with all of these issues as well as with the interactions between the activism of migrant women and that of European feminist activists. How far have the rights of migrant women been accounted for in national feminist activism within Europe?